2012
DOI: 10.2139/ssrn.2118511
|View full text |Cite
|
Sign up to set email alerts
|

Quantity or Quality? Collaboration Strategies in Research and Development and Incentives to Patent

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…While the literature on research and development (R&D) collaboration is significant (e.g., Faems et al, 2005;Hoekman et al, 2010;Hottenrott and Lopes-Bento, 2012;Letaifa and Rabeau, 2013;Freeman et al, 2014;Lin et al, 2014), literature specific to joint patenting is relatively scarce. Joint patenting, also known as copatenting, is a phenomenon in which more than one firm possesses full ownership of a patent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the literature on research and development (R&D) collaboration is significant (e.g., Faems et al, 2005;Hoekman et al, 2010;Hottenrott and Lopes-Bento, 2012;Letaifa and Rabeau, 2013;Freeman et al, 2014;Lin et al, 2014), literature specific to joint patenting is relatively scarce. Joint patenting, also known as copatenting, is a phenomenon in which more than one firm possesses full ownership of a patent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the panel study of Artz, Norman, Hatfield, and Cardinal (2010) on US firms' found that firms undertaking R&D were more likely to introduce patents. However, due to a lack of financial resources, SMEs can receive R&D support programs such as R&D subsidies, R&D grants or tax credit to accelerate their firm's performance (see, Hottenrott & Lopes-Bento, 2012). Further, Benavente and Goya (2012) conducted a microlevel qualitative study on Chilean firms' and found that the high unit cost of R&D, no tax incentives and the lack of R&D support programs are the major obstacles to Chilean SMEs.…”
Section: Obstacles To Firms' Innovationmentioning
confidence: 99%